2014
DOI: 10.1038/ncomms4721
|View full text |Cite
|
Sign up to set email alerts
|

Orbital resolution of molecules covalently attached to a clean semiconductor surface

Abstract: Understanding the chemical and electronic nature of molecules attached to semiconductors is of great importance in the study of molecule-based electronic devices. Resolving individual molecular orbitals using scanning tunnelling microscopy is a straightforward approach but remains challenging on the semiconductor surfaces because of their highly reactive dangling bonds. Here we show that hybridized molecular orbitals of pyridazine molecules covalently attached to Ge(100) surfaces can be resolved by scanning tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The production of well-defined layers is important to the organic functionalization of semiconductor surfaces and the application of the semiconductors in molecular electronics, sensors, thin-film displays, and fabricated hybrid devices. [1][2][3][4][5][6][7] Understanding the chemical reactions of organic compounds on semiconductor surfaces at the molecular level could enable the development of higher-performance hybrid devices incorporating organic and inorganic materials, as well as prediction of the reactivity between biomolecules and semiconductors. Extensive studies over the past two decades have revealed that under ultrahigh vacuum, various types of surface reactions that are analogous to organic reactions in the solution phase take place.…”
Section: Introductionmentioning
confidence: 99%
“…The production of well-defined layers is important to the organic functionalization of semiconductor surfaces and the application of the semiconductors in molecular electronics, sensors, thin-film displays, and fabricated hybrid devices. [1][2][3][4][5][6][7] Understanding the chemical reactions of organic compounds on semiconductor surfaces at the molecular level could enable the development of higher-performance hybrid devices incorporating organic and inorganic materials, as well as prediction of the reactivity between biomolecules and semiconductors. Extensive studies over the past two decades have revealed that under ultrahigh vacuum, various types of surface reactions that are analogous to organic reactions in the solution phase take place.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical modification of semiconductor surfaces via reaction with organic molecules has generated substantial interest because of its potential applications in the fabrication of molecule-based devices, biosensors, and organic dielectrics. The selectivity of the reaction pathway and the reaction site is crucial to such applications. Recently, solution-phase chemistry has been used to design new surface reactions under vacuum conditions to obtain specific substrate–adsorbate composite structures .…”
Section: Introductionmentioning
confidence: 99%
“…Aromaticity can be an important factor in determining product structure upon adsorption of organic molecules on solid surfaces, in that reaction pathways which break the aromaticity of the reactant are generally disfavored. 13 Adsorption of several N-containing aromatic heterocycles on the Ge(100)-2 × 1 surface, including pyrrole, 14,15 pyridine, 16−18 pyrimidine, 19 pyridazine, 20 thiazole, 21 hydroxypyridine and pyridone, 22 3-methyl-5-pyrazolone, 23 guanine, 24 and purine, 25 have been studied to date. As discussed above, the nitrogen moieties of these heterocycles show different reactivity upon adsorption; pyrrole undergoes N−H dissociation, 14,15 while molecules with pyridinic nitrogen form N−Ge dative bonds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Adsorption of several N-containing aromatic heterocycles on the Ge(100)-2 × 1 surface, including pyrrole, , pyridine, pyrimidine, pyridazine, thiazole, hydroxypyridine and pyridone, 3-methyl-5-pyrazolone, guanine, and purine, have been studied to date. As discussed above, the nitrogen moieties of these heterocycles show different reactivity upon adsorption; pyrrole undergoes N–H dissociation, , while molecules with pyridinic nitrogen form N–Ge dative bonds. Imidazole is a rigid five-membered aromatic heterocycle that possesses both pyrrolic (N 1 ) and pyridinic (N 3 ) nitrogens. The adsorption chemistry of a few molecules that include imidazole as part of their structure, but not that of imidazole itself, has been investigated on Group 14 semiconductor surfaces.…”
Section: Introductionmentioning
confidence: 99%